Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Let f(x) = - 5x + 6. Find and simplify f(3a-5).f(3a –5)=(Simplify your answer.)

Sagot :

Given:

[tex]f(x)=-5x+6[/tex]

We need to find f(3a-5)

So, substitute with x = 3a - 5 into the given function

So,

[tex]\begin{gathered} f(3a-5)=-5\cdot(3a-5)+6 \\ f(3a-5)=-5\cdot3a-5\cdot-5+6 \\ f(3a-5)=-15a+25+6 \\ \\ f(3a-5)=-15a+31 \end{gathered}[/tex]

so, the answer will be: f(3a-5) = -15a + 31